Analisa Kerentanan Wilayah Pesisir Meranti Dengan Metode CVI (Coastal Vulnerability Index) (Studi Kasus: Pulau Rangsang, Kabupaten Kepulauan Meranti) - Mourbas, Arin; Fauzi, Manyuk; Lilis, Yohanna (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Rangsang Island is one of the 4 main islands in the Meranti Islands Regency. The location of this island is very strategic because it is directly with the Malacca Strait so that this island has a very high economic value. Abrasion that occurred on Rangsang Island resulted in many losses experienced by people living on the coast of the island, including eroded coconut plantations, damaged docks, and people who were forced to evacuate because their homes were very prone to landslides. This condition is related to sea level rise due to global climate change, which makes these coastal areas vulnerable to disasters. This study aims to determine the vulnerability index of the coastal area of Rangsang Island based on oceanographic physical parameters (tidal and wave height) having a moderate level of vulnerability. Meanwhile, the sea level around the coast shows a high vulnerability. From the data obtained, the highest sea level rise was in Sonde village of 1.23 m and the lowest sea level rise was in Sungai Gayung Kiri village of 1.09 m. This value indicates that Sonde village has a high level of vulnerability in the category. This index variation shows that local changes on the coast of Mendol Island are correlated with global changes that occur, where local sea level rise is the impact of global ocean and climate changes.Keywords: Sea Level Rise, Wave Period and Height, Rangsang Island